An Electrically Reversible Switchable Surface to Control and Study Early Bacterial Adhesion Dynamics in Real-Time - Pranzetti, Alice; Mieszkin, Sophie; Iqbal, Parvez; Rawson, Frankie J.; Callow, Maureen E.; Callow, James A.; Koelsch, Patrick; Preece, Jon A.; Mendes, Paula M. (Advanced materials (Weinheim), 2013)
Bacterial adhesion can be controlled by applying electrical potentials to surfaces incorporating well‐spaced negatively charged 11‐mercaptoundecanoic acids. When combined with electrochemical surface plasmon resonance, these dynamic surfaces become powerful for monitoring and analysing the passage between reversible and non‐reversible cell adhesion, opening new opportunities to advance our understanding of cell adhesion processes.